Macrocyclic pyrrolobenzodiazepine dimers as antibody-drug conjugate payloads. Issue 23 (1st December 2017) - Donnell, Andrew F.; Zhang, Yong; Stang, Erik M.; Wei, Donna D.; Tebben, Andrew J.; Perez, Heidi L.; Schroeder, Gretchen M.; Pan, Chin; Rao, Chetana; Borzilleri, Robert M.; Vite, Gregory D.; Gangwar, Sanjeev
Graphical abstract: Abstract: Macrocyclic pyrrolobenzodiazepine dimers were designed and evaluated for use as antibody-drug conjugate payloads. Initial structure–activity exploration established that macrocyclization could increase the potency of PBD dimers compared with non-macrocyclic analogs. Further optimization overcame activity-limiting solubility issues, leading to compounds with highly potent (picomolar) activity against several cancer cell lines. High levels of in vitro potency and specificity were demonstrated with an anti-mesothelin conjugate.